1978
DOI: 10.1042/bj1740921
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin receptors on human platelets. Structure-activity relationships of stimulatory prostaglandins

Abstract: 1. Synthetic analogues of prostaglandins E2 or F2a, (monocyclic bisenoic prostaglandins), like the endogenous prostaglandin endoperoxides (prostaglandins G2 and H2) from platelets, and like synthetic analogues of prostaglandin H2 (bicyclic bisenoic prostaglandins), can induce aggregation of human platelets, although prostaglandins E2 and F2. themselves are inactive. 2. All the prostanoid compounds that induce platelet aggregation release 5-hydroxytryptamine from platelet dense bodies, but do not release f6-Nac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Our results are in agreement with those reported by MacIntyre et al [ 15]. Méth ylation of PGE2 at position C-15 or C-16 and substitution at C-9 led to substances with stimulatory activity on platelets at concentra tions up to 0.1 pmol/1 while PGE2 was inac tive.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are in agreement with those reported by MacIntyre et al [ 15]. Méth ylation of PGE2 at position C-15 or C-16 and substitution at C-9 led to substances with stimulatory activity on platelets at concentra tions up to 0.1 pmol/1 while PGE2 was inac tive.…”
Section: Discussionsupporting
confidence: 83%
“…After oral application of misoprostol, a 16-methyl derivative of PGE1; at doses used for gastric antiulcer therapy no changes of plate let function and bleeding time were found [14]. However, in vitro studies on human platelets have shown that PGEj derivatives with methylation at position 15 or 16 are able to induce aggregation and secretion [15].…”
Section: Introductionmentioning
confidence: 99%
“…This inhibitory action of each diastereoisomer could have been due either to the appearance at high concentrations of a separate inhibitory effect not specific for ADP, or to a low efficacy at the ADP receptor. No inhibitory action was found when platelets were aggregated in the presence of either diastereoisomer by 11,9-epoxymethano PGH2 ( Figure Id), which acts at a prostaglandin receptor (MacIntyre, Salzman & Gordon, 1978), and our evidence therefore suggests that (R)-ADP-a-S and (S)-ADPa-S are partial agonists, each with an intrinsic activity of 0.75, at the ADP receptor mediating aggregation of human platelets. This behaviour is similar to that of adenosine 5'-O-(2-thiodiphosphate) (ADP-,8-S), an ADP analogue in which a terminal (,3) phosphate oxygen is replaced by sulphur, which is also a partial agonist with an intrinsic activity of 0.75 as an aggregating agent (Cusack & Hourani, 1981).…”
Section: Discussionmentioning
confidence: 86%
“…After addition of an agonist to the stirred samples, reactions were terminated by adding 4 vol ice-cold 0.4% w/v EDTA in iso-osmotic saline, and immediate centrifugation (14,700 g; 20 °C; 1 min). Subsamples of cell free supernatant were taken for fluorimetric measurement of (3-N-acetyl-glucosaminidase (/3-NAG, a platelet lysosomal en zyme) and for radio-isotopic determination of (14C|-5-HT (a platelet-dense granule consti tuent), as described previously (31). A further subsample was taken for radioimmunoassay of (3-thromboglobulin (/3-TG, a platelet alpha granule constituent) (32).…”
Section: Methodsmentioning
confidence: 99%